OP0195 SELECTIVE EXPANSION OF REGULATORY T-CELLS IN HUMANS BY A NOVEL IL-2 CONJUGATE T-REG STIMULATOR, NKTR-358, BEING DEVELOPED FOR THE TREATMENT OF AUTOIMMUNE DISEASES. (June 2019) - Fanton, Christie; Siddhanti, Suresh; Dixit, Neha; Lu, Lin; Gordi, Toufigh; Dickerson, Daniel; Zalevsky, Jonathan; Kotzin, Brian
Abstract : Background: Impaired IL-2 production and dysfunction of regulatory T cells (Tregs) have been identified as key immunological defects leading to the breakdown of immune self-tolerance, a causative mechanism implicated in multiple autoimmune diseases. Enhanced sensitivity of Tregs to IL-2 supports the use of low-dose IL-2 therapy; however, this treatment is limited by its short half-life and relatively poor selectivity for stimulation of Tregs versus other T cell types. NKTR-358 is a polyethylene glycol (PEG) conjugate of recombinant human IL-2 (aldesleukin sequence with no additional amino acid mutation or substitution). It is differentiated from native IL-2 by its prolonged biological activity as well as its marked and selective stimulation of Tregs in different animal species, including non-human primates. Objectives: Study objectives assessed the safety and tolerability of NKTR-358 in humans administered single ascending doses subcutaneously (SC). In addition, time course and extent of changes in the numbers and percentages of Tregs, conventional CD4+ and CD8+ T cells, NK cells, cytokine levels, and the pharmacokinetics (PK) of NKTR-358 in peripheral blood were investigated. Methods: In this first-in-human, double-blind, single ascending dose study, healthy volunteers received SC doses ranging from 0.3 to 28 ug/kg (9 active:3 placebo per cohort) and subjects were followed for 50 days. Results: All 8 planned cohorts completed dosing. There were no dose-limiting toxicities, serious adverse events, deaths, or clinically significant abnormalities in vital signs, electrocardiograms, or laboratory test values. Adverse events attributed to NKTR-358 were primarily limited to mild (grade 1) injection site reactions. One subject at the highest dose tested demonstrated transient and mild (grade 1) symptoms of elevated cytokine levels and lymphopenia, which resolved without treatment. No other individual at any dose level had systemic signs or symptoms known to be associated with IL-2 therapy. The first 6 cohorts have been tested for anti-drug antibodies to date and none have been detected. NKTR-358 reached maximum plasma levels 4-6 days after administration, with little change for ∼2 weeks, and then decreased with a half-life of ∼ 8-9 days. NKTR-358 exhibited linear PK above the 1.0 ug/kg dose. The primary effect of NKTR 358 was seen on Tregs. In the 3.0 to 28.0 ug/kg dose cohorts, a dose-dependent and sustained increase in the absolute numbers and percentages of circulating CD4+FoxP3+CD25bright Tregs were observed. The elevated levels peaked at Days 10-12 and did not return to baseline until ∼ 20 to 25 days following administration. At 28.0 ug/kg, the mean peak increase in numbers of these CD25bright Tregs was 17-fold above baseline, and the mean peak percentage increased from 0.5% to 7.4%. In addition, there was an increase in Treg activation markers at doses ≥13.5 ug/kg. There was a mean increase of 3.5-fold in the percentages and numbers of NK cells at the highest dose tested, but no changes in percentages or numbers of conventional CD4+ or CD8+ T cells were observed. NKTR-358 selectively induced Tregs, evidenced by a 15-fold increase in the mean peak Treg:CD8 ratio over baseline in the 28.0 ug/kg group. Conclusion: Single doses of the IL-2 conjugate T-reg stimulator, NKTR-358, in the dose range tested were well tolerated and safe. NKTR-358 led to a striking and selective dose-dependent increase in circulating CD25bright Tregs with minimal effects on conventional T cells and with relatively small effects on NK cells. These clinical results extend previous animal studies showing the prolonged and Treg selective action of NKTR-358, and provide strong support for testing NKTR-358 as a new therapeutic in autoimmune diseases, such as systemic lupus. Disclosure of Interests: Christie Fanton Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Suresh Siddhanti Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Neha Dixit Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Lin Lu Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Toufigh Gordi Shareholder of: Nektar Therapeutics, Consultant for: Rosa & Co LLC, Employee of: Nektar Therapeutics, Daniel Dickerson Speakers bureau: Last speaking engagement was 2013, Jonathan Zalevsky Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Brian Kotzin Shareholder of: Nektar Therapeutics, Gilead Sciences, Amgen, Rigel Pharmaceuticals, Consultant for: Nektar Therapeutics, Employee of: Nektar Therapeutics